BUDGET PADDING AND NATIONAL DEVELOPMENT IN NIGERIA - Oloto, Sunday Emeka; Nnamani, Desmond Okechukwu; Nnamani, Kevin S (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2019)
The concept of budget padding was new in 2016 dictionary of Nigeria politics. This entrench budgetary process over the years as billions of naira was illegally padded through inflating the budget to trillions of naira and this has derailed the objectives of the budget preparation suspiciously. It has been observed that budget padding came in due to conflict of interest between the subordinate and superior, principal and agent, legislature that gain advantageous information against Nigerian masses. Budget padding is a persistent corruption, act of illicit enrichment of limited funds or resources that undermines policy changes for socio-economic development in Nigeria. This new budgetary act has led to poverty, inequality, unemployment, destitution, diseases, illiteracy and poor living standard among citizens. This paper examined budget padding and national development in Nigeria. The paper is anchored on prebendalism theory as its framework using qualitative method. The paper in its findings, opined that lawmakers inserted whooping sum in the budget, certain funds proposed by the executive for key infrastructures were either removed from the budget or slashed by the National Assembly and this corrupt action undermine national development. The abnormal conduct of budget padding by national assembly is a national embarrassment and it has imposed a lot of moral disgrace on Nigerian State. It is on this premise that the paper recommend that there is need for presidency to engage consulting firm to audit the financial bill to ensure accountability and hitch free budget preparation.